The Influence of Guru Penggerak Programs and Komunitas Penggerak in Improving the Quality of Elementary School Education through School Digitization - Birgitta Resty Yulianaji (AL-ISHLAH: Jurnal Pendidikan, 2023)
Teachers' failure to see themselves as change agents is a significant issue in the modern world. Teachers can lose sight of their noble calling to educate the nation's future if they are not properly supervised. It is hoped that the guru penggerak Programme and the komunitas penggerak will help Indonesia speed up its efforts to improve the quality of its educational system. The research methodologies used in this investigation are quantitative and descriptive in nature. Two hundred people from seven elementary schools in cluster 7, Depok District, Sleman Regency, participated in this study as administrators, teachers, students, parents, community leaders, and representatives of educational organisations. The questionnaire employed in this study was a type of research instrument. Classical assumption tests (for normality, multicollinearity, and Glejser heteroscedasticity), route analysis tests, and hypothesis tests were utilised in the inferential data analysis method. This study found that the impact of the guru penggerak on student learning was less significant than the impact of the driving instructor on student learning via school digitisation.